PENGARUH KOMPENSASI MOTIVASI DAN KOMPETENSI TERHADAP KEPUASAN KERJA BERDASARKAN PERSEPSI KARYAWAN PT DAVIDI INTERNASIONAL DI BALIKPAPAN : THE INFLUENCE OF MOTIVATION COMPENSATION AND COMPETENCE ON JOB SATISFACTION BASED ON THE PERCEPTIONS OF EMPLOYEESPT DAVIDI INTERNATIONAL IN BALIKPAPAN - Nainggolan, Hermin; Anggraini, Melly (Sekolah Tinggi Ilmu Ekonomi Balikpapan, 2024)
This study aims to determine the effect of compensation, motivation and competence on job satisfaction based on the perceptions of employees of PT Davidi Internasional in Balikpapan, either partially or simultaneously. The number of samples is 65 respondents. Data collection was carried out using primary data by distributing questionnaires directly to respondents. Data were analyzed by validity and reliability tests as well as multiple linear analysis, F test (simultaneous), t test (partial) and classical assumptions. The results showed that it was simultaneously proven that the variables of compensation, notivation and competence had a positive and significant effect on job satisfaction based on the perceptions of employees of PT Davidi Internasional in Balikpapan Partially the compensation variable (XI) had a positive and significant effect on job satisfaction (Y), partially the variable motivation (X2) has a positive and significant effect on job satisfaction (Y), partially the compensation variable (X3) has a negative and insignificant effect on job satisfaction (Y) at PT Davidi Internasional in Balikpapan.